The Intervention Effects of Common Dietary Patterns on Polycystic Ovary Syndrome - Wu, Yezhen (Exploring Science Academic Conference Series, 2026)
The intervention effects of common dietary patterns on poly-cystic ovary syndrome (PCOS) are a common endocrine and metabolic disease in women of reproductive age with symptoms such as insulin resistance (IR), hyperandrogenemia, infertility, and so on. In recent years, the incidence rate of PCOS has been rising steadily. The exact causes of leading to the disease are still unknown, but it is presumed that it is associated with dietary patterns. However, dietary intervention as a first-line non-drug intervention strategy plays an important role in improving PCOS symptoms. Thus, from dietary aspects, the paper systematically investigated the research progress, clinical application, and limitations from the three core dietary patterns—the Mediterranean diet, ketogenic diet, and low-carbohydrate diet in the intervention of PCOS, which provided a reference for the formulation of individualized clinical nutritional interventions.